Imaging spectrum of immunomodulating, chemotherapeutic and radiation therapy related intracranial effects - Lincoln, Christie Mary; Fata, Peter; Sotardi, Susan; Pohlen, Michael; Uribe, Tomas; Bello, Jacqueline A. (British journal of radiology, 2018)
A wide range of treatment-related side effects result in specific neurologic symptoms and signs and neuroimaging features. Even to the most seasoned neuroradiologist, elucidating therapy-related side effects from other common mimics can be challenging. We provide a pictorial survey of some common and uncommon medication-induced and therapy-related neuroimaging manifestations, discuss pathophysiology and common pitfalls in imaging and diagnosis. A case-based review is utilized to depict scenarios on a routine basis in a general radiology or neuroradiology practice such as medication-induced posterior reversible encephalopathy syndrome to the more challenging cases of pseudoprogression and pseudoregression in temozolmide and bevacizumab therapy in gliobastoma treatment protocols. Knowledge of the treatment-induced imaging abnormalities is essential in the accurate interpretation and diagnosis from the most routine to most challenging of clinical situations. We provide a pictorial review for the radiologist to employ in order to be an invaluable provider to our clinical colleagues and patients.